Modern techniques for TMJ evaluation - Modjaw versus Cadiax - a systematic review - Cristina Mihai; Mariana Păcurar; Emilia Prodea; Iulia Dumitrescu; Iuliana-Irina Nedelcu (Romanian Journal of Stomatology)
The temporomandibular joint (TMJ) plays a crucial role in various functions of the jaw, including chewing, speaking, and swallowing. Disorders of the TMJ can significantly impact a patient's quality of life, causing pain, dysfunction, and other systemic issues. Comprehensive TMJ evaluation is essential for accurately diagnosing and effectively treating these disorders. Two modern techniques for TMJ evaluation, Modjaw and Cadiax, offer advanced tools for detailed assessment. This comparison explores the capabilities, methodologies, and benefits of each system based on the current published studies. The aim is to highlight the novel nature of using digitalized tools for diagnosis and treatment planning, ass well as assessing the reliability of two systems.